The Impact of AI-Assisted Role Play on Ecosystem Learning to Improve Cognitive and Communication Skills - Rofiah, Siti Hafifatul; Rochintaniawati, Diana; Sinaga, Parlindungan (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study addresses the need to improve students’ cognitive and communication skills in science learning, particularly in understanding ecosystem interactions. In Indonesia, these competencies remain low due to limited student-centered learning strategies. This research aimed to examine the impact of AI-assisted role play as an innovative instructional approach to enhance these skills. A quasi-experimental design with a control group pretest-posttest was applied. The study was conducted in one junior high school in Cimahi on May 5, 2025, involving 22 seventh-grade students in an experimental class. The treatment involved AI-generated role play scenarios to simulate ecological interactions. Data were collected using cognitive achievement tests and communication skill rubrics. The analysis used paired and independent sample t-tests. The results revealed a significant improvement in students’ posttest scores, indicating enhanced conceptual understanding of ecosystem components and ecological relationships. Moreover, students showed improvement in oral communication, collaboration, and scientific reasoning. However, the cognitive improvement was not highly significant, likely due to the limited learning duration and stronger emphasis on affective and social aspects during role play. These findings suggest that AI-assisted role play can support contextual and engaging science learning, particularly in developing communication competence. The study concludes that integrating interactive AI tools within science classrooms holds promise for enhancing scientific literacy in line with the goals of the Merdeka Curriculum.